SWOT Analysis as a Destination Management Tool in the Context of the New Economy - Miriam GARBAROVA; Lukas VARTIAK (Communications of International Proceedings, 2021)
To be competitive in the new economy, it is necessary to think and plan strategically. The critical factor is creating a destination's strategic plan, which summarises the destination's future goals and set goals on these bases. A strategic tool, SWOT analysis, can be used to set strategic goals and evaluate destination assumptions through destination management when creating a tourism product. The paper aims to determine the conditions for further regional tourism development in the selected Region through SWOT analysis. Information compiled from primary and secondary research was used to carry out a SWOT analysis in the given Region and fulfil the paper's aim.
Keywords: Destination Management; SWOT Analysis; Region; Development; New Economy.